The Impact of Digital Literacy and Communication on Employee Performance via Work Motivation - Supriyadi Supriyadi; Ni Made Dwi Puspitawati; Gde Bayu surya Parwita; Agus Wahyudi Salasa gama (AIBPM Publisher, 2025)
Digital transformation demands that organizations strengthen their digital literacy culture and internal communication to enhance workforce performance. This research investigates the impact of digital literacy culture and communication on employee performance, with work motivation serving as a mediating variable. Using a quantitative method, data were collected from 45 employees via a Likert-scale survey. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) version 4.0 was employed for data analysis. Findings reveal that digital literacy culture and communication both have substantial positive effects on workforce performance, with path coefficients of 0.292 and 0.331, respectively. Additionally, work motivation significantly influences performance (? = 0.487) and partially mediates the connections among the independent variables and workforce performance. This study highlights the essential significance of digital literacy culture in improving workforce performance through motivation. The results suggest that fostering digital skills and effective communication can boost motivation, ultimately leading to better performance. Organizations are advised to adopt strategies promoting digital literacy and communication to sustain performance improvements.